Disease-causing 7.4 kb cis-regulatory deletion disrupting conserved non-coding sequences and their interaction with the FOXL2 promotor: implications for mutation screening. - Barbara D'haene; Catia Attanasio; Diane Beysen; Josée Dostie; Edmond Lemire; Philippe Bouchard; Michael Field; Kristie Jones; Birgit Lorenz; Björn Menten; Karen Buysse; Filip Pattyn; et al. (PLoS Genetics)
To date, the contribution of disrupted potentially cis-regulatory conserved non-coding sequences (CNCs) to human disease is most likely underestimated, as no systematic screens for putative deleterious variations in CNCs have been conducted. As a model for monogenic disease we studied the involvement of genetic changes of CNCs in the cis-regulatory domain of FOXL2 in blepharophimosis syndrome (BPES). Fifty-seven molecularly unsolved BPES patients underwent high-resolution copy number screening and targeted sequencing of CNCs. Apart from three larger distant deletions, a de novo deletion as small as 7.4 kb was found at 283 kb 5' to FOXL2. The deletion appeared to be triggered by an H-DNA-induced double-stranded break (DSB). In addition, it disrupts a novel long non-coding RNA (ncRNA) PISRT1 and 8 CNCs. The regulatory potential of the deleted CNCs was substantiated by in vitro luciferase assays. Interestingly, Chromosome Conformation Capture (3C) of a 625 kb region surrounding FOXL2 in expressing cellular systems revealed physical interactions of three upstream fragments and the FOXL2 core promoter. Importantly, one of these contains the 7.4 kb deleted fragment. Overall, this study revealed the smallest distant deletion causing monogenic disease and impacts upon the concept of mutation screening in human disease and developmental disorders in particular.